OP0237 Lifitegrast ophthalmic solution 5.0% for treatment of dry eye disease: combined evidence from 5 randomized controlled trials. (15th June 2017) - Baudouin, C; Darvish-Zargar, M; Holland, EJ; Chan, CC; Nichols, KK; Tauber, J; Raychaudhuri, A; Roy, M; Shojaei, A
Abstract : Background: Dry eye disease (DED) is a multifactorial disease of the tear film and ocular surface, characterized by ocular discomfort and visual disturbance. 1 DED is associated with a number of systemic autoimmune diseases, particularly rheumatoid arthritis and Sjögren's syndrome. 2, 3 Lifitegrast is a lymphocyte function-associated antigen-1 (LFA-1) antagonist that inhibits T-cell–mediated inflammation (an underlying factor in DED) and is approved in the US for the treatment of signs and symptoms of DED (lifitegrast ophthalmic solution 5.0%, Xiidra®). Objectives: To evaluate the combined evidence from 5 clinical trials of lifitegrast ophthalmic solution 5.0% (LIF) in subjects with dry eye disease (DED). Methods: Adults with DED were randomized to LIF or placebo (PBO) in 5 randomized, double-masked, placebo-controlled trials: 4 12-week efficacy/safety studies (phase 2, LIF n=58, PBO n=58; phase 3 trials: OPUS-1, LIF n=293, PBO n=295; OPUS-2, LIF n=358, PBO n=360; OPUS-3, LIF n=355, PBO n=356), and a 1-year safety study (SONATA, LIF n=220, PBO n=111). Individuals with secondary Sjögren's syndrome associated with autoimmune disease (eg, rheumatoid arthritis, systemic lupus erythematosus) were eligible to participate if they were not immunodeficient/immunosuppressed, not taking steroids, and met all other inclusion and exclusion criteria. Change from baseline to day 84 in DED signs and symptoms was evaluated across the 12-week studies. Key measures were inferior corneal staining score (ICSS; 0–4 scale), eye dryness score (EDS; visual analogue scale [VAS], 0–100 scale), and visual-related function subscale of a symptom scale (0–4 scale). Pooled safety data (LIF n=1287, PBO n=1177) from all 5 trials were also analyzed. Results: LIF improved ICSS versus PBO in the phase 2 study (secondary endpoint; treatment effect 0.35, nominal P =0.0209), OPUS-1 (co-primary; 0.24, P =0.0007), and OPUS-3 (ad hoc; 0.17, nominal P =0.0144). LIF reduced EDS (VAS) versus PBO in OPUS-2 (co-primary; 12.61, P <0.0001) and OPUS-3 (primary; 7.16, P =0.0007). The OPUS-1 co-primary symptom endpoint of visual-related function subscale, and the OPUS-2 co-primary sign endpoint of ICSS, did not achieve statistical significance. In the pooled safety analysis, total exposure was 415.65 person-years for LIF, and 332.15 person-years for PBO. Adverse events were mostly mild or moderate in severity. There were no serious ocular treatment-emergent adverse events (TEAEs) and withdrawals due to TEAEs were infrequent (LIF, 7.0%; PBO, 2.6%). Conclusions: LIF improved signs and symptoms of DED in adults with DED and appeared to be well tolerated with no serious ocular TEAEs reported. References: DEWS. Ocul Surf. 2007;5:75–92. Fujita M et al. Am J Ophthalmol. 2005;140:808–13. Patel SJ, Lundy DC. Am Fam Physician. 2002;66:991–8. Acknowledgements: This study was sponsored by SARcode Bioscience (now a wholly owned subsidiary of Shire PLC) and Shire Development LLC. Disclosure of Interest: C. Baudouin Consultant for: Alcon Laboratories, Inc., Allergan, Dompé, Horus Pharma, Santen Inc., Thea Pharmaceuticals, M. Darvish-Zargar Consultant for: Allergan, Novartis, Abbott Medical Optics, E. Holland Grant/research support from: Alcon Laboratories Inc., Allergan, Mati Therapeutics, Omeros, PRN, Senju Pharaceuticals, Consultant for: Alcon Laboratories Inc., Allergan, Bausch & Lomb, Kala Pharmaceuticals, Mati Therapeutics, Omeros, PRN, RPS, Senju Pharaceuticals, Shire/SARcode, TearLab, TearScience, Speakers bureau: Alcon Laboratories Inc., Allergan, Bausch & Lomb, Omeros, Senju Pharaceuticals, Shire/SARcode, TearScience, C. Chan Grant/research support from: Allergan, Bausch and Lomb, TearLab, Consultant for: Allergan, Bausch & Lomb, Alcon Labs Inc., TearScience, K. Nichols Grant/research support from: Kala Pharmaceuticals, Shire PLC, TearScience, Vistakon, Consultant for: Allergan, InSite Vision Inc., Kala Pharmaceuticals, Parion Sciences, Santen, ScienceBased Health, Shire PLC/SARcode, J. Tauber Consultant for: Allergan, Bausch & Lomb, Shire PLC, Senju Pharaceuticals, Speakers bureau: Shire/SARcode, A. Raychaudhuri Employee of: Shire PLC (at the time of the study), M. Roy Employee of: Shire PLC, A. Shojaei Employee of: Shire PLC